2000
DOI: 10.1161/01.cir.101.19.2284
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Hemodynamic Responses to Environmental Thermal Stress Among Adolescents

Abstract: Background-Previous studies by our laboratory and others have shown that blood pressure (BP) responses to many short-term laboratory stressors are greater in black than in white children. We sought to determine the cardiac and vascular contributions to these differences in BP reactivity and whether racial differences in vascular reactivity involve excessive vasoconstriction or deficient vasodilation. Methods and Results-We evaluated BP, heart rate, and impedance cardiographic measures of preejection period (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…These findings are consistent with studies showing few atherosclerotic changes in the large arteries of patients with small vessel disease 23 and hyperinsulinaemia in black, but not white, hypertensive subjects with end organ damage. 15 Increased carotid intima media thickness 24 and attenuated vascular reactivity 10,14 but better large vessel function [25][26][27][28] have been described in Afro-Caribbeans previously, but this is the first study in which all of these aspects have been examined together in community settings. Explanations for population differences in disease susceptibility must be sought in representative samples of the general population to ensure unbiased and generalizable comparisons.…”
Section: Discussionmentioning
confidence: 70%
“…These findings are consistent with studies showing few atherosclerotic changes in the large arteries of patients with small vessel disease 23 and hyperinsulinaemia in black, but not white, hypertensive subjects with end organ damage. 15 Increased carotid intima media thickness 24 and attenuated vascular reactivity 10,14 but better large vessel function [25][26][27][28] have been described in Afro-Caribbeans previously, but this is the first study in which all of these aspects have been examined together in community settings. Explanations for population differences in disease susceptibility must be sought in representative samples of the general population to ensure unbiased and generalizable comparisons.…”
Section: Discussionmentioning
confidence: 70%
“…Cardiac output, TPR, and TPC were estimated with thoracic impedance using the Kubicek equation (13). This method of estimating cardiac output has previously been used under heat-stressed condition (11,19). We recognize that this method of cardiac output measurement, and thus the calculation of TPR and TPC, has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Impedance cardiograph and phonocardiography (models EBI 100C and DA 100, Biopac System, Santa Barbara, CA) were used to measure transthoracic impedance (Zo) and left ventricular ejection time for the estimation of stroke volume. This noninvasive method to measure stroke volume has been widely used under both normothermic and heat stress conditions (3,11,13,19). Forearm skin blood flow was indexed by laser-Doppler flowmetry (Perimed, North Royalton, OH) from an area not covered by the tube-lined suit.…”
Section: Subjectsmentioning
confidence: 99%
“…In support of this, prior studies showed that endothelium-dependent vasodilatation was impaired in black individuals as compared to white individuals, even in young, otherwise healthy adults. [27][28][29][30][31] Further, individuals of African descent may be at higher risk for renal sodium retention, resistant hypertension, and vascular injury due to a number of factors such as a higher prevalence of primary aldosteronism or activating polymorphisms in renal tubular epithelial sodium channels. These factors, in turn, may partially explain racial differences in the association between albuminuria and stroke in this study.…”
Section: Figurementioning
confidence: 99%